No surface breaking on the Ecemiş Fault, central Turkey, since Late Pleistocene (~64.5ka); new geomorphic and geochronologic data from cosmogenic dating of offset alluvial fans - Sarıkaya, M.A.; Yıldırım, C.; Çiner, A. (Elsevier BV, 2015)
Abstract The Ecemis Fault Zone (EF) has been recognized as a major left lateral strike-slip fault in the Central Anatolian Fault Zone (CAFZ) of Turkey. However, its Quaternary slip-rate has been challenging to determine due to the difficulty of dating offset markers. Using high-precision offset measurements and 36 Cl cosmogenic nuclide dating, we present the first geochronologically determined Late Quaternary slip-rate for the EF. Our study focuses on the excellent exposures of offset alluvial fan surfaces, originating from the Aladaglar, a Late Quaternary glaciated mountain. Analysis of airborne orthophotogrametry and GNSS (Global Navigation Satellite System) surveys indicates 168 ± 2 m left lateral and 31 ± 1 m vertical displacements. In-situ terrestrial cosmogenic 36 Cl geochronology obtained from eleven surface boulders provides a minimum abandonment/incision age of 104.2 ± 16.5 ka for the oldest offset alluvial fan surface. Our geomorphic observations together with Self-potential geophysical surveys revealed the presence of an unfaulted alluvial fan terrace, which allows us to constrain the timing of deformation. The abandonment/incision age of this fan is 64.5 ± 5.6 ka based on thirteen 36 Cl depth profile samples. Accordingly, we obtained a geologic fault slip-rate of 4.2 ± 1.9 mm a − 1 horizontally and 0.8 ± 0.3 mm a − 1 vertically for the time frame between 104.2 ± 16.5 ka and 64.5 ± 5.6 ka. Our analysis indicates that the EF has not been producing a major surface breaking earthquake on the main strand at least since 64.5 ± 5.6 ka (mid-Late Pleistocene). This could be the result of abandonment of the main strand and accommodation of deformation by other faults within the EF. Nevertheless, a recently occurred (30 September 2011) low magnitude (ML: 4.3) left lateral strike-slip earthquake indicates recent seismic activity of the EF. Comparison of the recent GPS velocity field with the longer slip history along the CAFZ indicates a constant but low strain release without surface breaking and very long large earthquake recurrence intervals.